Creencias acerca del abuso sexual infantil de los operadores judiciales (2020)
The purpose of this investigation is to characterize the beliefs about child sexual abuse (ASI) of judicial operators, taking as a sample 46 of them who are or are working in cases of ASI and hold positions as Judicial Police, Psychologists, Lawyers or Social Workers. The area of psychology in which this research is framed is legal psychology and the line of coexistence, Peace and Justice, and to the sub-line Relations Individual-State, Democracy and Citizenship. However, regarding the methodological aspects, this research is based on the empirical-analytical paradigm, being of a non-experimental, transversal and descriptive quantitative type and implementing the non-probabilistic type of sampling. Finally, in the results, it was concluded that the beliefs that had the highest incidence among the participants of the investigation were those of item 17 (children who do not reveal sexual abuse is because they want or want sexual contact to continue) and the item 19 (sexual assailants of minors have mental problems), it can also be evidenced that the Judicial Police were the ones who had the greatest misconceptions about ASI and it was found that there is no significant difference between the beliefs of ASI that men and women possess Sample participants.